Rescue technique for endoscopic extraction of biliary stent with proximal migration: “zipline – forceps” - Quiroga-Purizaca, Wilmer Gustavo (2024)
The endoscopic placement of a biliary stent presents adverse events, including proximal migration in the bile duct, a situation that can be so challenging to resolve that surgery must sometimes be resorted to. We present the case of a 83-year-old patient who underwent endoscopic retrograde cholangio pancreatography (ERCP) for acute cholangitis and a plastic biliary stent was placed for stenosis in the distal common bile duct. Four months later, proximal migration of the stent was evident; conventional extraction techniques were performed without success. Due to not having a cholangioscope, a novel method was designed in which a forceps is slid along a hydrophilic guide and guided to the distal portion of the stent in order to successfully trap and extract it. It is concluded that the “zipline” technique is an effective method that could be used safely in patients with proximal migration of a biliary stent in which its adherence to the biliary wall does not allow it to be linked with common methods, especially in situations where direct cholangioscopy is not available.